Large-scale biomedical science : exploring strategies for future research - Nass, Sharyl J.; Stillman, Bruce (National Academies Press, 2003)
The nature of biomedical research has been evolving in recent years. Technological advances that make it easier to study the vast complexity of biological systems have led to the initiation of projects with a larger scale and scope. In many cases, these large-scale analyses may be the most efficient and effective way to extract functional information from complex biological systems. "Large-Scale Biomedical Science: Exploring Strategies for Future Research looks at the role of these new large-scale projects in the biomedical sciences. Though written by the National Academies' Cancer Policy Board, this book addresses implications of large-scale science extending far beyond cancer research. It also identifies obstacles to the implementation of these projects, and makes recommendations to improve the process. The ultimate goal of biomedical research is to advance knowledge and provide useful innovations to society. Determining the best and most efficient method for accomplishing that goal, however, is a continuing and evolving challenge. The recommendations presented in "Large-Scale Biomedical Science are intended to facilitate a more open, inclusive, and accountable approach to large-scale biomedical research, which in turn will maximize progress in understanding and controlling human disease